The role of supply chain resilience on SMEs' performance: The case of an emerging economy - Mohammed Awad Alshahrani; Mohammad Asif Salam (Logistics, 2022)
Existing studies have predominantly explored the influence of supply chain resilience on the performance of firms in the context of developed economies. This study highlights the need for SMEs to be prepared to tackle uncertainties in business operations. Background: Small and Medium Enterprises (SMEs) play a critical role in every economy, and limited studies have highlighted the significance of resilience in the firms. Therefore, this study aims to determine the impact of supply chain resilience on SMEs' performance in Saudi Arabia based on three dimensions of resilience, namely agility, robustness, and flexibility. It aims to investigate how they relate to the dimensions of SMEs' performance, namely production performance and market/sales performance. This study also investigates the overall impact of supply chain resilience as a construct on SMEs' performance. Methods: This study employed a quantitative research design to answer the research questions. A self-administered questionnaire was used to collect data. The study was based on 255 samples of managers in SMEs from Saudi Arabia. The hypothesized model has been tested using the SPSS/Amos 26. Results: Based on the findings, it has been found that supply chain agility and flexibility had a significant positive relationship with SMEs' production and marketing/sales performances. Supply chain robustness demonstrated a significant positive relationship with SMEs' production performance but not their marketing/sales performances. Overall, there was a significant positive relationship between supply chain resilience and SMEs' performance. Conclusions: This study contributes to the body of literature on supply chain resilience by expounding knowledge on aspects such as agility, flexibility, and robustness. The study enhances our understanding of the role of supply chain resilience on SMEs' performance in an emerging economy context.
Keywords: 650; agility; flexibility; performance; resilience; robustness; Saudi Arabia; SME